2012
DOI: 10.1007/s12032-012-0217-9
|View full text |Cite
|
Sign up to set email alerts
|

Melanoma with unknown primary: report and analysis of 24 patients

Abstract: In the literature, there are some papers reporting on patients with metastatic melanoma from an unknown primary lesion (MUP). The pathogenesis of this phenomenon and the prognosis of these patients are still debatable. Therefore, we reviewed our casistics on MUP patients. We identified 24 MUP patients out of all patients registered into a melanoma database from June 1996 to June 2011. The incidence was 1.4%. We compared the survival rate of all patients with MUP stage III-IV with all patients with metastatic m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 60 publications
1
6
0
Order By: Relevance
“…Our study found that the average age at biopsy for people who reported tanning bed usage was significantly lower compared to those who had not reported using a tanning bed but that age at biopsy was not found to be significant associated with 5 year OS. Characteristics of tanning bed users in our cohort were consistent with other studies, Caucasian women 1 with a young age at presentation. 2…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our study found that the average age at biopsy for people who reported tanning bed usage was significantly lower compared to those who had not reported using a tanning bed but that age at biopsy was not found to be significant associated with 5 year OS. Characteristics of tanning bed users in our cohort were consistent with other studies, Caucasian women 1 with a young age at presentation. 2…”
Section: Discussionsupporting
confidence: 91%
“…No primary site is identified in 1% to 8% of all melanomas. 1 Questions remain about MUP reflecting effective immune clearance of the cutaneous primary lesion, and our finding may implicate a detrimental effect on immune clearance induced by tanning bed exposure. This finding requires further exploration in clinical and basic studies.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…MUP is by definition a metastatic melanoma [1] . After Das Gupta et al [3] had first defined MUP criteria, many authors investigated the prognosis of this entity with conflicting results [1,[9][10][11] .…”
Section: Discussionmentioning
confidence: 99%
“…The overall survival of patients with MUP who present with lymph node involvement or visceral organ disease is no worse than, and is perhaps better than, the overall survival of patients with MKP who have stage III or stage IV disease, respectively. 132,135,136 Adjuvant therapy…”
Section: Melanoma Of Unknown Primary (Mup)mentioning
confidence: 99%